Roughness in Hypervector Spaces. (11th March 2022) - Abughazalah, Nabilah; Yaqoob, Naveed; Usman, Muhammad
Abstract : This paper examines rough sets in hypervector spaces and provides a few examples and results in this regard. We also investigate the congruence relations-based unification of rough set theory in hypervector spaces. We introduce the concepts of lower and upper approximations in hypervector spaces.